Some Cases of Root Exegesis of Hebrew Forms in Peshitta Ezekiel - Lund, Jerome A. 1948- (2019)
The new translation of Peshitta Ezekiel by Gillian Greenberg and Donald M. Walter in the Bible of Antioch series raises issues with regard to the interpretation of the Syriac text and its relationship to the Hebrew. The Syriac translator used root exegesis of Hebrew forms as a translation tool. This study will examine a number of cases of root exegesis in Peshitta Ezekiel with the aim of better understanding the Peshitta translation. This research was undertaken as part of the Bible of Edessa project.
Keywords: Bible of Antioch; BIBLE OF EDESSA; Hebrew lexicography; Peshitta Old Testament; Syriac Old Testament; derivation of Hebrew forms; exegesis of Hebrew forms; translation technique